INTRODUCTION TO THE HISTORY OF KASHTACHIL ART AND METHODS OF SEWING (Conference Zone, 2022)
The article provided theoretical information on the concept and history of embroidery art, the originality of embroidery, the use of tools, flowers and patterns, the choice of colors.